PENERAPAN BALANCED SCORECARD SEBAGAI TOLAK UKUR PENGUKURAN KINERJA PADA ORGANISASI NIRLABA - Arofah, Dewi; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to test and to analyze the performance of RA. Basoeni Regional General Hospitals Mojokerto based on learning and growth perspective, internal business perspective, customer perspective and financial perspective by using the Balanced Scorecard method. The research objects are RA. Basoeni Regional General Hospitals Mojokerto in 2014 and 2015 which requires 80 patients and 50 employees as the respondents who have been selected by using purposive sampling. The data collection techniques have been done by performing preliminary survey, questionnaires, literary study, documentation, and interview. The method has been done by using descriptive qualitative analysis. The result of the research shows that RA. Basoeni Regional General Hospitals Mojokerto have had clear vision, mission, strategic goals and objectives. In 2014 and 2015 the average performance on learning and growth perspective is quite good since the numbers of employees decrease, the performance of the internal business perspective both when it is reviewed from inpatients in the surgery process, the performance on customer perspective because it shows patients satisfied with the provided services and perspective finances is better but it is still less economical in the use of the budget.Keywords: balanced scorecard, growth and learning perspective, internal business perspective, customer perspective and finance.